The moderating role of personality traits in the relationship between interoception and somatic symptoms in youth: a predictive processing perspective - Eichhorn, Henrik; Leydecker, L. Eileen; Brand, Sebastian; Jungmann, Stefanie M. (BMC Psychology, 2025)
Objective: Somatic symptoms are highly prevalent in youth, but the treatment effectiveness for somatic symptom disorder is limited and the underlying mechanisms are incompletely understood. According to a predictive coding approach, low interoceptive accuracy (i.e., accuracy in perceiving internal signals from the body) may relate to somatic symptoms. So far, a potential moderating effect of personality factors on this relationship has been unexplored. Neuroticism and perfectionism could play a major role in this moderation in that they could shape expectations to be more pessimistic. This study examines the connection of neuroticism and perfectionism with interoception as well as with somatic symptoms in adolescents. Method 172 adolescents (aged 14–21) completed psychometric questionnaires assessing interoceptive accuracy, somatic symptoms, as well as levels of neuroticism and perfectionism in a cross-sectional survey. Results: Increased neuroticism was associated with reduced interoceptive accuracy (r = –.25, p = .003), whereas the relationship between perfectionism and interoceptive accuracy did not reach significance (r = –.17, p = .053). Furthermore, neuroticism and perfectionism were each associated with more somatic symptoms (r = .39, p < .001; r = .23, p = .006). Neither neuroticism nor perfectionism moderated the relationship between interoceptive accuracy and somatic symptoms (ΔR² = 0.06%, p = .794; ΔR² = 0.92%, p = .510). Conclusion: We discuss the results in the context of a predictive processing approach for the development of somatic symptoms and the need for further research.
Gesehen am 24.02.2026